2017
DOI: 10.1136/bmjsem-2017-000237
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma injections for symptomatic tendinopathy: systematic review and meta-analysis of randomised injection-controlled trials

Abstract: AimTo determine the efficacy of platelet-rich plasma (PRP) injections for symptomatic tendinopathy.DesignSystematic review of randomised, injection-controlled trials with meta-analysis.Data sourcesSystematic searches of MEDLINE and EMBASE, supplemented by manual searches.Eligibility criteria for selecting studiesRandomised controlled trials with 3 months minimum follow-up that evaluated pain reduction with PRP versus control (saline, local anaesthetic, corticosteroid) injections in patients with symptomatic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 41 publications
0
65
0
2
Order By: Relevance
“…Injection of PRP in these patients may have reduced the carpal tunnel tendon and MN inflammation present in this cohort, thus benefitting, not only the muscles innervated by the distal branches of the MN, but all the irrigated flexor tendons within the carpal tunnel which are the primarily responsible for transferring tensile loads to hand grip (digitorum profundus and superficialis tendons). In this sense, several in vitro and in vivo studies have shown that PRP has anti-inflammatory effects and improves tendon healing, and have elucidated its molecular mechanism of action in this context [51][52][53][54][55][56][57][58][59][60][61] . Nonetheless, other human studies reported that PRP had no beneficial effects on tendon healing [62][63][64][65][66] , or only found them after longer follow-ups [67][68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…Injection of PRP in these patients may have reduced the carpal tunnel tendon and MN inflammation present in this cohort, thus benefitting, not only the muscles innervated by the distal branches of the MN, but all the irrigated flexor tendons within the carpal tunnel which are the primarily responsible for transferring tensile loads to hand grip (digitorum profundus and superficialis tendons). In this sense, several in vitro and in vivo studies have shown that PRP has anti-inflammatory effects and improves tendon healing, and have elucidated its molecular mechanism of action in this context [51][52][53][54][55][56][57][58][59][60][61] . Nonetheless, other human studies reported that PRP had no beneficial effects on tendon healing [62][63][64][65][66] , or only found them after longer follow-ups [67][68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…In the first stage of screening titles and abstracts, 79 references were selected. Full texts were scrutinised against the inclusion and exclusion criteria, with a final inclusion of 29 SRs (Figure ) . Reasons for exclusion of studies at the second stage are presented by topic and clinical indication in Files …”
Section: Resultsmentioning
confidence: 99%
“…Three SRS assessing the clinical efficacy of PRP for the treatment of different types of tendinopathies were identified . These SRs presented variable methodological quality (AMSTAR scores from 4 to 12).…”
Section: Resultsmentioning
confidence: 99%
“…However, substantial heterogeneity was reported at baseline and different time-point follow-ups. Miller et al [79] included 16 RCTs with a minimum follow-up of three months. PRP was more effective than controls in reducing pain with a moderate effect size (0.47, 95%CI (0.22-0.72, p < 0.001)) and moderate heterogeneity.…”
Section: Tendinopathiesmentioning
confidence: 99%
“…However, this conclusion is barely supported by the studies taken individually. Miller et al [79] attributed the discrepancy to the fact that studies are underpowered (median 35 patients per group) to detect the effect size. According to their meta-analysis, a sample size of 73 patients per group would be required to be able to detect differences.…”
Section: Tendinopathiesmentioning
confidence: 99%